Oral Care for a Better Quality of Life: A Nursing Guideline to Prevent Oral Mucositis in Pediatric Cancer Patients - Maipimai, Maneerat; Thongkhla, Sarinya (Princess of Naradhiwas University Journal, 2026)
Oral mucositis is a common and severe side effect in pediatric cancer patients undergoing Oral mucositis is a common and severe side effect in pediatric cancer patients undergoing chemotherapy. It causes significant pain and discomfort, impacting eating, communication, and treatment plans and potentially leading to additional infections and even death. This academic article aimed to present nursing guidelines for preventing oral mucositis. The content included the mechanism of oral mucositis development, risk factors, risk assessment, and nursing guidelines for prevention and promoting oral care behaviors that can be applied to develop clinical practice guidelines to effectively reduce the incidence and severity of oral mucositis in pediatric cancer patients. These recommendations will also help improve the quality of life for pediatric cancer patients and their families.